Study Association of CA15-3, CEA with Vitamin D3 in Patients Suffering from Breast cancer - Hassan, Mohamed Hadi; Abdul-Hassan, Layla S. (Medical Science Journal for Advance Research, 2024)
Background: The study aims to determine the relationship between CEA and CA15-3 with Vitamin D3 among breast cancer patients. purpose: The study aims to explore the relationship between CEA and CA15-3 with Vitamin D3 in breast cancer patients and hypothesizes that Vitamin D3 may influence these biomarkers related to cancer prognosis. Methods: Conducted at the National Oncology Teaching Hospital in Najaf Governorate from September 2023 to March 2024, the study included 90 breast cancer patients and 90 controls. Serum levels of CA15-3, CEA, and Vitamin D3 were measured using ELISA, with statistical analysis performed using SPSS version 25. Results: The study found significant negative correlations between Vitamin D3 levels and the biomarkers CEA (r = -.422, p = .001) and CA15-3 (r = -.499, p = .001). Breast cancer patients had significantly lower Vitamin D3 levels (9.22 ± 0.07 ng/mL) than controls (35.62 ± 0.02 ng/mL, p = .0001). CA15-3 and CEA levels were significantly higher in patients compared to controls. Implications The findings suggest that Vitamin D3 may regulate tumor markers, impacting breast cancer outcomes and therapy. This supports the potential use of Vitamin D3 supplementation in breast cancer treatment. Conclusion: our study indicated that the level of Vitamin D3 was inversely related to both CEA and CA15-3 whereby a high level of Vitamin D3 corresponded to the low level of these tumor markers This investigation highlights the need to ensure required Vitamin D3 levels in these patients with breast cancer and indicates that administration of Vitamin D3 could be a promising intervention strategy in the management of the Breast Cancer.